Effect of Mordant Bleaching on the Optical and Mechanical Properties of Black Tunisian Wool and Optimization of the Bleaching Process - Takwa Bouagga; Taoufik Harizi; Faouzi Sakli (Journal of Natural Fibers, 2022)
White wool occupies a very important place on the commercial market because it can be dyed in any color. In nature, however, wool fibers are usually found white but may be black; sometimes they are shades of white, yellow and, in some cases, brown or black, because of their natural pigment, melanin. In this study, copper sulfate and iron sulfate were used in the treatment of Tunisian wool (Black of Thibar) to evaluate their effectiveness in terms of color removal and minimal damage to wool fibers. Once the most effective mordant agent was chosen, the effects of hydrogen peroxide concentration, bleaching time, and temperature on the wool sample bleaching were studied. The results showed that iron sulfate is the most effective mordant agent in the bleaching process of pigmented wool for a good base of dyeing and finishing, since it guarantees the best optical properties with the minimum damage to the fibers. In addition, it was found that the optimal bleaching was achieved for a hydrogen peroxide concentration of 87.5 mL/L, a treatment time of about 90 min and a temperature of about 60°C.